AND: OR: IF…THEN: IFF: (P⊃Q) and (Q⊃P) from (P≡Q) (P v Q) and ~(P·Q) from ~(P≡Q) Steps: 1. Reverse squiggles (mark the line) 2. Drop existentials (mark the line) - ∃x 3. Drop universals (don't mark the line) – x ∃x become x vice versa: ~(x)Lx → (∃x)~Lx ~(∃x)Lx→(x)~Lx Add constant: (∃x)(Rx·Bx) → (Ra·Ba) However, cannot: (∃x)(Fx·(x)Gx) → (Fa·(x)Gx) (Ex) Px-> Pa // can only be used once, need to use new constants afterwards (x)Bx -> Ba // can be used multiple times, use the old constants 1. Each quantifier – All are R = (x)Rx – Not all are R= ~(x)Rx – Some are R = there is an R = (∃x)Rx, – Nothing is R = there is no R = ~(∃x)Rx Derived line generates a contradiction, next line is to infer the negation of the latest assumption Test 1: Test 2: Test 3: Test 4: Test 5: Test 6: Test 7: Test 8: